Comprehensive Genomic Profiling of Rare Tumors: Routes to Targeted Therapies - Wang, Shuhang; Chen, Rongrong; Tang, Yu; Yu, Yue; Fang, Yuan; Huang, Huiyao; Wu, Dawei; Fang, Hong; Bai, Ying; Sun, Chao; Yu, Anqi; Fan, Qi; et al. (Frontiers in Oncology, 2020)
Comprehensive Genomic Profiling may be informative for novel treatment strategies and to improve outcomes for patients with rare tumors. This study aims to discover opportunities for use of targeted therapies currently in routine practice in patients with rare tumors. We defined rare tumors in China, pulled genomic data of 4901 patient with rare tumors from cBioPortal, and retrospectively analyzed next-generation sequencing (NGS) genomic profiling data of a second cohort of 1312 patients with rare tumors from across China. Data availability and presence of targetable genomic alterations (TGAs) in patient populations from cBioPortal and our cohort were compared. We created a China-specific definition of “rare tumors” which included 141 tumor subtypes. Subsequently, we queried cBioPortal and obtained 63 subtypes of rare tumor according to our definition. A second, independent cohort of Chinese patients included 67 subtypes. Forty-one subtypes were common between the two cohorts, and we lacked genetic information for 52 out of 141 rare tumor types. The prevalence of TGAs was 20.40% (1000/4901) in cBioPortal cohort, and 53.43% (701/1312) in our cohort, which is significantly higher. Generally, targetable mutations in BRAF, BRCA2, CDKN2A, EGFR, ERBB2, KIT, MET, NF1, ROS1 were 3 or more times more frequent in our Chinese cohort compared with that of the cBioPortal cohort. Cancer of unknown primary tumor type, gastrointestinal stromal tumor, gallbladder cancer, intrahepatic cholangiocarcinoma, and sarcomatoid carcinoma of the lung were among the top 5 tumors with the highest incidence of targetable genomic alterations. Rare tumors in China was defined for the first time. Genomic profiling of rare tumors according to that definition from cBioPortal and an independent Chinese showed substantial targetable genomic alterations, which was substantially higher in Chinese rare tumor patient population.